Discovery of Lymantini weevils (Coleoptera: Curculionidae: Molytinae) outside the Americas: Devernodes, a new genus for five new species from Southeast Asia - Grebennikov, Vasily V. (Zootaxa, 2018)
This paper reports a new weevil genus Devernodes gen. n. established for five new species from Southeast Asia: D. alkippe sp. n. (China: Mt. Emei), D. asteria sp. n. (Vietnam: Tam Dao), D. chthonia sp. n. (Vietnam: Tam Dao; the type species), D. drimo sp. n. (Malaysia: Pasoh Forest Reserve) and D. methone sp. n. (Malaysia: Tanah Rata). All Devernodes are wingless and inhabit the forest leaf litter. Adult Devernodes share a combination of two head characters unique among weevils in Asia: antenna with apparently unsegmented club and 6-segmented antennal funicle, as well as strong constriction separating the eye-bearing rostrum from the head capsule. To test monophyly and investigate phylogenetic relationships of Devernodes, Maximum Likelihood phylogenetic analysis was undertaken using parts of mitochondrial (COI) and nuclear ribosomal (28S) genes, as well as the nuclear internal transcribed spacer (ITS2) from 14 Devernodes and 55 outgroup Curculionidae specimens. Results strongly corroborated monophyly of Devernodes and did not suggest its realistic sister-group. The new genus is assigned to the molytine tribe Lymantini (not represented in the DNA analysis) based on two potential synapomorphies: head markedly constricted behind eyes and presence of undivided female hemisternites IX (= “merged coxite and stylus”). Thus interpreted, Devernodes is the twelfth nominal genus of Lymantini and the first record of the tribe outside of the Americas. All original data (localities, DNA sequences, specimen images) are available online in public datasets dx.doi.org/10.5883/DS-DEVERNO1 and dx.doi.org/10.5883/DS-DEVERNO2.